2010
DOI: 10.1002/hep.23944
|View full text |Cite
|
Sign up to set email alerts
|

Radioembolization with Yttrium-90 Glass Microspheres in Hepatocellular Carcinoma: European Experience on Safety and Long-Term Survival

Abstract: Radioembolization has been demonstrated to allow locoregional therapy of patients with hepatocellular carcinoma not eligible for transarterial chemoembolization or other local therapies. The aim of this study was to validate evidence of the safety and efficacy of this treatment in a European sample of patients with advanced hepatocellular carcinoma (HCC). Therefore, 108 consecutive patients with advanced HCC and liver cirrhosis were included. Yttrium-90 (Y-90) microspheres were administered in a lobar fashion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

23
300
4
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 408 publications
(349 citation statements)
references
References 22 publications
23
300
4
12
Order By: Relevance
“…The toxicity profile of glass microspheres was shown to be acceptable in the Lambert et al study, in line with previously published reports [2][3][4]. The risk of pulmonary toxicity is effectively detected by MAA scintigraphy, and patients presenting pulmonary risks are systematically excluded from therapy.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…The toxicity profile of glass microspheres was shown to be acceptable in the Lambert et al study, in line with previously published reports [2][3][4]. The risk of pulmonary toxicity is effectively detected by MAA scintigraphy, and patients presenting pulmonary risks are systematically excluded from therapy.…”
supporting
confidence: 82%
“…Their report confirms that this technique may be utilised by teams with no prior experience in the use of microspheres, without major complications and with comparable efficacy results. In fact, while taking into account tumour necrosis, Lambert et al reported an objective response rate of 50%, in line with previous results published by Salem et al [2] (57% in a series involving 291 patients) and Hilgard et al [3] (40% in a series involving 108 patients).…”
supporting
confidence: 73%
See 2 more Smart Citations
“…Studies from Europe and the United States, comprised of 776 patients in aggregate, have demonstrated comparable results when taking into account cohort differences in terms of baseline Child-Pugh classification and tumor stage defined by the Barcelona Clinic Liver Cancer system (BCLC) [1][2][3][4]. These Western studies included patients predominately with hepatitis C and/or alcohol as the underlying cause of liver disease with limited numbers of patients with hepatitis B virus (HBV) (9-30 %).…”
mentioning
confidence: 99%